Crystal form of compound maleate as well as preparation method and application of crystal form
By reacting with acid, the salt type of compound I was prepared, and its stability and solubility problems were solved, and the bioavailability of the drug and the simplicity of production were improved.
Patent Information
- Application Number
- CN202311339796.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2024-12-20
AI Technical Summary
Compound I lacks the pharmaceutically acceptable salt type and crystalline form, resulting in poor physical and chemical stability, strong hygroscopicity and low solubility, which affects the storage and production process of drugs.
By reacting with acids such as p-toluenesulfonic acid, maleic acid, benzenesulfonic acid, citric acid, hydrochloric acid and hydrobromic acid, salt types of compound I with excellent physical and chemical stability and high solubility are prepared, such as maleate salts, such as maleate salts. Crystal Form A.
It improves the solubility and stability of Compound I, reduces hygroscopy, enhances the bioavailability and safety of the drug, simplifies the preparation production process, and maintains the purity and morphology of the drug under different conditions.
Smart Images

Figure CN119161312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of crystal chemistry, and in particular to pharmaceutically acceptable salts of Ethanone, 1-[4-(trifluoromethyl)phenyl]-, O-[3-(1-piperidinyl)propyl]oxime and their crystal forms. Background Art
[0002] Ethanone,1-[4-(trifluoromethyl)phenyl]-,O-[3-(1-piperidinyl)propyl]oxime has a structure of formula (I), which is referred to herein as compound I.
[0003]
[0004] The structure and preparation method of Compound I are disclosed in Example 49 of CN111848549B. The patent text also discloses potential therapeutic areas for the use of Compound I.
[0005] In the development of small molecule drugs, drug polymorphism is a common phenomenon in drug research and development and an important factor affecting drug quality. A crystal is a solid in which compound molecules are arranged in a three-dimensional orderly manner in a microstructure to form a lattice. Polymorphism refers to the phenomenon that a compound exists in multiple crystal forms. A compound may exist in one or more crystal forms, but its existence and properties cannot be specifically predicted. The changes in properties caused by different crystal forms can also improve the final formulation form. For example, this change can increase solubility and thus improve bioavailability, or improve the stability of the active ingredient, or more unexpectedly, while increasing solubility, have good stability and lower hygroscopicity. For the above-mentioned compound I, it is necessary to further study and improve its different crystal forms. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defect of compound I lacking pharmaceutically acceptable salt form and crystal form and to improve its physical and chemical properties, thereby providing a pharmaceutically acceptable salt of the compound as shown in formula (I), which may be a hydrate, an anhydrate or a crystalline or amorphous form of a solvate.
[0007] Wherein, the pharmaceutically acceptable salt of Compound I can be an organic acid salt or an inorganic acid salt, and further, is selected from p-toluenesulfonate, maleate, benzenesulfonate, citrate, hydrochloride or hydrobromide, etc.
[0008] Applicants have discovered solid forms of the p-toluenesulfonate, maleate, benzenesulfonate, citrate, hydrochloride or hydrobromide salts of Compound I that are physically and chemically stable over a range of storage conditions and that can be subjected to additional processing.
[0009] The pharmaceutically acceptable salt of Compound I provided by the present invention, such as p-toluenesulfonate, maleate, benzenesulfonate, citrate, hydrochloride or hydrobromide, has a molar ratio of organic acid or inorganic acid to Compound I of preferably 1:2-2:1, more preferably 1:1.
[0010] The pharmaceutically acceptable salt of Compound I provided by the present invention, such as p-toluenesulfonate, maleate, benzenesulfonate, citrate, hydrochloride or hydrobromide, is preferably a crystalline solid.
[0011] The present invention provides a pharmaceutically acceptable salt of Compound I, such as p-toluenesulfonate, maleate, benzenesulfonate, citrate, hydrochloride or hydrobromide.
[0012] The present invention provides a maleate salt of Compound I.
[0013] Furthermore, the present invention provides a crystalline form of a maleate salt of Compound I (hereinafter referred to as "crystalline form A").
[0014] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of Form A is substantially as follows Figure 2 shown.
[0015] Without limitation, the thermogravimetric analysis / differential scanning calorimetry analysis diagram of Form A is substantially as follows Figure 3 The results show that when the crystal form A is heated to 100°C, it has only a 0.11% mass loss and an endothermic peak begins to appear around 115.0°C.
[0016] Without limitation, Form A is an anhydrate.
[0017] Without limitation, the X-ray powder diffraction pattern of the crystalline form A has diffraction angles 2θ of 9.52°±0.2°, 10.44°±0.2°, 12.82°±0.2°, 15.85°±0.2°, 17.17°±0.2°, 17.51°±0.2°, 19.08°±0.2°, 19.56°±0.2°, 19.99°±0.2°, 20.72°±0.2°, 20.95°±0.2°. There are characteristic peaks at any one, or 2, or 3, or 4, or 5, or 6, or 7, or 8, or 9, or 10, or 11, or 12, or 13, or 14, or 15, or 16, or 17 of 2°, 21.45°±0.2°, 23.07°±0.2°, 23.58°±0.2°, 27.18°±0.2°, 28.89°±0.2°, and 30.06°±0.2°.
[0018] The present invention provides a p-toluenesulfonate salt of Compound I.
[0019] Furthermore, the present invention provides a crystalline form of the p-toluenesulfonate salt of Compound I (hereinafter referred to as "crystalline form C").
[0020] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of Form C is substantially as follows Figure 5 shown.
[0021] Without limitation, the thermogravimetric analysis / differential scanning calorimetry analysis diagram of Form C is substantially as follows Figure 6 As shown, the results show that when the crystal form C is heated to 150°C, there is a 0.62% mass loss and an endothermic peak begins to appear near 153.8°C.
[0022] Without limitation, the X-ray powder diffraction pattern of the crystalline form C has characteristic peaks at any one of the diffraction angles 2θ of 6.06°±0.2°, 9.51°±0.2°, 12.07°±0.2°, 12.77°±0.2°, 15.07°±0.2°, 17.59°±0.2°, 18.05°±0.2°, 19.04°±0.2°, 20.24°±0.2°, 23.03°±0.2°, 28.79°±0.2°, 30.38°±0.2°, and 36.63°±0.2°, or 2, or 3, or 4, or 5, or 6, or 7, or 8, or 9, or 10, or 11, or 12, or 13.
[0023] The present invention provides a benzenesulfonate salt of compound I.
[0024] Furthermore, the present invention provides a crystalline form of a benzenesulfonate salt of Compound I (hereinafter referred to as "crystalline form D").
[0025] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of Form D is substantially as follows Figure 8 shown.
[0026] Without limitation, the thermogravimetric analysis / differential scanning calorimetry analysis diagram of Form D is substantially as follows Fig. 9 As shown, the results show that when the crystal form D is heated to 150°C, there is a 0.11% mass loss, and an endothermic peak begins to appear around 130.7°C.
[0027] Without limitation, the X-ray powder diffraction pattern of the crystalline form D has diffraction angle 2θ values of 6.31°±0.2°, 11.89°±0.2°, 12.58°±0.2°, 15.56°±0.2°, 16.98°±0.2°, 17.35°±0.2°, 17.76°±0.2°, 18.20°±0.2°, 18.46°±0.2°, 19.86°±0.2°, 20.57°±0.2°, 20.76°±0.2°, 21 There are characteristic peaks at any one, or 2, or 3, or 4, or 5, or 6, or 7, or 8, or 9, or 10, or 11, or 12, or 13, or 14, or 15, or 16, or 17, or 18, or 19 of .96°±0.2°, 22.29°±0.2°, 23.11°±0.2°, 23.42°±0.2°, 24.39°±0.2°, 26.16°±0.2°, and 26.49°±0.2°.
[0028] The present invention provides a citrate salt of Compound I.
[0029] Furthermore, the present invention provides a crystalline form of a citrate salt of Compound I (hereinafter referred to as "crystalline form E").
[0030] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of Form E is substantially as follows Fig.10 shown.
[0031] Without limitation, the thermogravimetric analysis / differential scanning calorimetry analysis diagram of Form E is substantially as follows Fig.11 As shown, the results show that Form E has a mass loss of 1.45% when heated to 100°C, and there is an endothermic peak at 85.8°C (peak temperature).
[0032] Without limitation, the X-ray powder diffraction pattern of the crystalline form E has characteristic peaks at any one of the diffraction angles 2θ of 4.05°±0.2°, 12.02°±0.2°, 12.37°±0.2°, 13.78°±0.2°, 16.04°±0.2°, 17.78°±0.2°, 18.53°±0.2°, 19.08°±0.2°, 20.07°±0.2°, 22.79°±0.2°, 24.58°±0.2°, and 24.83°±0.2°, or 2, or 3, or 4, or 5, or 6, or 7, or 8, or 9, or 10, or 11.
[0033] The present invention provides the hydrobromide salt of Compound I.
[0034] Furthermore, the present invention provides a crystalline form of the hydrobromide salt of Compound I (hereinafter referred to as "crystalline form F").
[0035] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of Form F is substantially as follows Fig.12 shown.
[0036] Without limitation, the thermogravimetric analysis / differential scanning calorimetry analysis diagram of Form F is substantially as follows Fig.13 As shown, the results indicate that Form F has a mass loss of 2.26% when heated to 150°C, and has two endothermic peaks at 72.2 and 172.7°C (peak temperatures).
[0037] Without limitation, the X-ray powder diffraction pattern of the crystalline form F has a diffraction angle 2θ value of 5.38°±0.2°, 10.70°±0.2°, 12.10°±0.2°, 14.40°±0.2°, 15.56°±0.2°, 16.06°±0.2°, 17.03°±0.2°, 17.36°±0.2°, 17.77°±0.2°, 19.14°±0.2°, 20.07°±0.2°, 21.29°±0.2°, 21.54°±0.2°, 22.64°±0.2°, 23. There are characteristic peaks at any one, or 2, or 3, or 4, or 5, or 6, or 7, or 8, or 9, or 10, or 11, or 12, or 13, or 14, or 15, or 16, or 17, or 18, or 19, or 20, or 21 of 0.2°, 22.97°±0.2°, 23.44°±0.2°, 23.65°±0.2°, 24.55°±0.2°, 26.88°±0.2°, 27.44°±0.2°, and 27.64°±0.2°.
[0038] Technical Effects
[0039] Compound I is often in a viscous oily liquid state, and only becomes an amorphous solid when placed for a long time (>24h) at low temperature (<-20°C), and has the disadvantages of strong hygroscopicity, poor physicochemical stability, poor solubility, and high solvent residue, which not only increases the drug safety risk, but also increases the cost of drug production. In order to improve the physicochemical stability of Compound I and reduce its hygroscopicity, the applicant conducted a salt formation study on Compound I. For example, the inventors of the present application used hippuric acid, D-tartaric acid, L-pyroglutamic acid, L-malic acid, methanesulfonic acid, phosphoric acid, sulfuric acid, fumaric acid, formic acid, succinic acid, p-toluenesulfonic acid, maleic acid, benzenesulfonic acid, citric acid, hydrochloric acid and hydrobromic acid to react with Compound I in order to obtain a salt form of Compound I suitable for pharmaceutical use.
[0040] The relevant salt-forming reactions are shown in Table 9 of Example 2. The results show that hippuric acid, D-tartaric acid, L-pyroglutamic acid, L-malic acid, methanesulfonic acid, phosphoric acid, sulfuric acid, fumaric acid, formic acid, and succinic acid do not form corresponding salts with compound I, or the obtained products are oily, which fails to significantly improve the above-mentioned shortcomings of compound I.
[0041] In order to further study the pharmaceutically acceptable salts of Compound I, the inventors of the present application made great efforts to prepare p-toluenesulfonate, maleate, benzenesulfonate, citrate, hydrochloride and hydrobromide of Compound I. As shown in Table 15 of Example 10, after comparing the stability, TGA / DSC and yield of the salt forms of Compound I, it can be seen that Compound I maleate, Compound I hydrochloride and Compound I p-toluenesulfonate are preferred salt forms with good physicochemical stability and high yield.
[0042] Further research on Compound I maleate crystal form A, Compound I hydrochloride crystal form B and Compound I p-toluenesulfonate crystal form C revealed that compared with crystal forms B and C, crystal form A can maintain higher solubility while having good stability and lower hygroscopicity, with excellent overall effects. Specifically, crystal form A has the following unexpected technical effects:
[0043] (1) Compared with Form C, Form A has higher solubility. Form A has high solubility in water, SGF, FaSSIF and FeSSIF (>6.5 mg / mL), and the crystal form does not change before and after testing in different solvents. Form C has low solubility in water, SGF and FaSSIF (1-2 mg / mL). The Form A provided by the present invention has higher solubility, which is beneficial to improve the absorption of drugs in the human body and improve bioavailability; in addition, higher solubility can reduce the dosage of drugs while ensuring the efficacy of drugs, thereby reducing the side effects of drugs and improving the safety of drugs.
[0044] High temperature and high humidity conditions caused by seasonal differences, climate differences in different regions and environmental factors will affect the storage, transportation and production of raw materials. Form A has better stability under accelerated conditions, which is helpful to avoid the impact on drug quality due to crystal transformation or purity reduction during drug storage.
[0045] (2) Compared with Form B, Form A has lower moisture gain. The moisture gain of Form B at 0% RH-80% RH is 3.285%, while the moisture gain of Form A at 0% RH-80% RH is only 0.331%. Under the same conditions, the moisture gain of Form A is only 1 / 10 of that of Form B, and the crystal form of Form A does not change after one cycle of 0% RH-95% RH-0% RH. This indicates that Form A has weaker hygroscopicity and better humidity stability.
[0046] Strong hygroscopicity can easily cause chemical degradation and crystal transformation of APIs, thus directly affecting the physical and chemical stability of APIs. In addition, strong hygroscopicity can reduce the fluidity of APIs, thus affecting the processing technology of APIs. On the other hand, drugs with strong hygroscopicity need to maintain low humidity during production and storage, which places higher requirements on production and requires high costs.
[0047] (3) After being placed at 25°C / 60%RH and 40°C / 75%RH for 1 week and 2 weeks, the crystal form of Form A did not change, and the chemical purity did not change during storage; after being placed at 80°C for 24 hours, the crystal form did not change, indicating that Form A has good physical and chemical stability under accelerated and harsh conditions. The crystal form of Form A did not change after being exposed to strong light for 10 days, indicating that Form A has good light stability.
[0048] High temperature and high humidity conditions caused by seasonal differences, climate differences in different regions and environmental factors will affect the storage, transportation and production of raw materials. Form A has better stability under accelerated conditions, which is helpful to avoid the impact on drug quality due to crystal transformation or purity reduction during drug storage.
[0049] (4) SEM and PLM results show that Form A is a flaky crystal, and the particle size distribution shows that Form A has a relatively uniform particle size distribution. Flaky crystals have excellent filtration performance and are more conducive to preparation production. At the same time, uniform particle size helps to ensure content uniformity and reduce the variability of in vitro dissolution, while simplifying the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 XRPD pattern of amorphous compound I
[0051] Figure 2 XRPD diagram of Form A
[0052] Figure 3 TGA / DSC diagram of Form A
[0053] Figure 4 For the crystal form A 1 H NMR diagram
[0054] Figure 5 XRPD diagram of Form C
[0055] Figure 6 TGA / DSC diagram of Form C
[0056] Figure 7 For the crystal form C 1 H NMR spectra
[0057] Figure 8 XRPD diagram of Form D
[0058] Fig. 9 TGA / DSC diagram of Form D
[0059] Fig.10 XRPD diagram of Form E
[0060] Fig.11 TGA / DSC diagram of Form E
[0061] Fig.12 XRPD diagram of Form F
[0062] Fig.13 TGA / DSC diagram of Form F
[0063] Fig.14 DVS diagram of Form A
[0064] Fig.15 XRPD comparison of Form A before and after DVS test (top: before test, bottom: after test)
[0065] Fig.16 PLM diagram of Form A
[0066] Fig.17 SEM image of Form A
[0067] Fig.18 DVS diagram of Form B
[0068] Fig.19 XRPD comparison of Form A before and after storage under different conditions (from top to bottom: starting Form A, 25°C / 60% RH for 1 week, 25°C / 60% RH for 2 weeks, 40°C / 75% RH for 1 week, 40°C / 75% RH for 2 weeks)
[0069] Fig. 20 The particle size distribution diagram of Form A
[0070] Fig.21 XRPD comparison of Form C before and after storage under different conditions (from top to bottom: starting Form C, 25°C / 60% RH for 1 week, 25°C / 60% RH for 2 weeks, 40°C / 75% RH for 1 week, 40°C / 75% RH for 2 weeks) Specific implementation plan
[0071] The present invention is described in detail with reference to the following examples, which describe in detail the preparation and use of the crystalline forms of the present invention. It will be apparent to those skilled in the art that many changes in both materials and methods may be made without departing from the scope of the present invention.
[0072] The abbreviations used in the present invention are explained as follows:
[0073] XRPD: X-ray powder diffraction
[0074] DSC: Differential Scanning Calorimetry
[0075] TGA: Thermogravimetric analysis
[0076] 1 HNMR: Liquid Hydrogen Nuclear Magnetic Spectroscopy
[0077] RH: Relative humidity
[0078] PLM: Polarized Light Microscopy
[0079] DVS: Dynamic Water Sorption
[0080] HPLC: High Performance Liquid Chromatography
[0081] 1 H Solution NMR: Hydrogen solution NMR
[0082] SEM: Scanning Electron Microscope
[0083] The XRPD spectrum was collected on an X-ray powder diffraction analyzer from PANalytical, and the XRPD parameters are shown in Table 1.
[0084] Table 1
[0085]
[0086] TGA was collected on a TA 5500 thermogravimetric analyzer, and DSC was collected on a TA 2500 and TA 250 differential scanning calorimeters. The test parameters are shown in Table 2.
[0087] Table 2
[0088] parameter TGA DSC method Linear temperature rise Linear temperature rise Sample tray Aluminum tray, open Aluminum tray, with cover or without cover Temperature range Room temperature - set the end point temperature 25℃-Set the end temperature Scan rate (℃ / min) 10 10 Protective gas Nitrogen Nitrogen
[0089] Dynamic moisture sorption (DVS) curves were collected on SMS (Surface Measurement Systems) DVS Intrinsic and DVS Intrinsic plus. The relative humidity at 25°C was measured using LiCl, Mg(NO 3 )2 and KCl deliquescence point correction. The DVS test parameters are shown in Table 3.
[0090] Table 3
[0091]
[0092] In this application, the purity test, dynamic solubility and stability test were conducted by high performance liquid chromatography, and the ion salt molar ratio test was conducted by Thermo AQ RFIC ion chromatograph. The analysis conditions were as follows:
[0093] Table 4 HPLC test conditions (purity test method)
[0094]
[0095]
[0096] Table 5 HPLC test conditions (solubility test method of Form C)
[0097]
[0098] Table 6 HPLC test conditions (solubility test method of Form A)
[0099]
[0100]
[0101] Table 7 Ion chromatography test conditions
[0102]
[0103] Liquid NMR spectra were collected on a Bruker 400M or Bruker 600M NMR instrument. 6 or CDCl 3 As a solvent.
[0104] Polarized light microscopy data were acquired with an Axio Lab.A1 upright microscope at room temperature.
[0105] Scanning electron microscopy was performed using a Phenom pure+ instrument (Phenom, The Netherlands).
[0106] The particle size distribution of the samples was tested using Mastersizer 3000 (Malvern, UK). The measurement parameters are shown in Table 8.
[0107] Table 8
[0108]
[0109]
[0110] The "centrifugation" is accomplished by conventional methods in the art, such as centrifugation or filtration. The operation of "centrifugation" is: placing the sample to be separated in a centrifuge tube and centrifuging at a rate of 10,000 rpm until all the solids sink to the bottom of the centrifuge tube.
[0111] The "volatilization" is accomplished by conventional methods in the art, for example, slow volatilization is to seal the container with a sealing film, pierce holes, and allow the container to volatilize; rapid volatilization is to leave the container open for volatilization.
[0112] The "drying" is accomplished by conventional methods in the art, such as vacuum drying, forced air drying or natural air drying. The drying temperature can be room temperature or higher, preferably room temperature to about 60°C, or to 50°C, or to 40°C. The drying time can be 2-48 hours, or. The drying is carried out in a fume hood, forced air oven or vacuum oven.
[0113] The "stirring" is accomplished by conventional methods in the art, such as magnetic stirring or mechanical stirring, with a stirring speed of 50-1800 rpm, wherein the magnetic stirring speed is preferably 300-900 rpm, and the mechanical stirring speed is preferably 100-300 rpm.
[0114] The "room temperature" is not a specific temperature value, but refers to the temperature range of 10-30°C.
[0115] The "anhydrous substance" refers to a solid substance that does not contain crystal water or crystallization solvent.
[0116] The "hydrate" refers to a solid substance containing water of crystallization.
[0117] The “characteristic peak” refers to a representative diffraction peak used to identify crystals. When tested using Cu-ka radiation, the peak position can usually have an error of ±0.2°.
[0118] In the present invention, "crystal" or "crystal form" can be characterized by X-ray powder diffraction. The XRPD diffraction data of the crystal has fingerprint properties. Different crystal forms are identified in the art based on the diffraction data of XRPD. Those skilled in the art will select several representative peaks in the XRPD spectrum as characteristic peaks to characterize the crystal, and the peak position, peak intensity and peak shape are comprehensively considered when selecting characteristic peaks. However, those skilled in the art will understand that the X-ray powder diffraction pattern is affected by the conditions of the instrument, the preparation of the sample and the purity of the sample. The peak intensity of the diffraction peak in the X-ray powder diffraction pattern may also change with changes in experimental conditions. In fact, the peak intensity of the diffraction peak in the X-ray powder diffraction pattern is related to the preferred orientation of the crystal. The diffraction peak intensity shown in the present invention is illustrative rather than for absolute comparison. Therefore, when identifying whether the crystal forms are the same, the matching of the peak positions within the above error range is the first priority.
[0119] It is understood by those skilled in the art that the X-ray powder diffraction pattern of the crystal form protected by the present invention does not have to be completely consistent with the X-ray powder diffraction patterns in the embodiments referred to herein, and any crystal form having an X-ray powder diffraction pattern that is identical or similar to the characteristic peaks in these patterns falls within the scope of the present invention. Those skilled in the art can compare the X-ray powder diffraction pattern listed in the present invention with the X-ray powder diffraction pattern of an unknown crystal form to confirm whether the two sets of patterns reflect the same or different crystal forms.
[0120] In some embodiments, the maleate, p-toluenesulfonate, benzenesulfonate, citrate, hydrochloride or hydrobromide of Compound I of the present invention and its crystalline form are pure, substantially without any other crystalline form mixed. In the present invention, "substantially without" when used to refer to a new crystalline form means that this crystalline form contains less than 20% (by weight) of other crystalline forms, especially less than 10% (by weight) of other crystalline forms, more less than 5% (by weight) of other crystalline forms, and more less than 1% (by weight) of other crystalline forms.
[0121] The term "about" in the present invention, when used to refer to a measurable value, such as mass, time, temperature, etc., means that there is a certain floating range around the specific value, which can be ±10%, ±5%, ±1%, ±0.5%, or ±0.1%. DETAILED DESCRIPTION
[0123] Example 1 Characterization of Compound I
[0124] Compound I is a viscous oil at room temperature and solidifies at -20°C. The XRPD patterns of the samples at room temperature and after solidification are as follows: Figure 1 As shown, the results indicate that compound I is amorphous.
[0125] Example 2 Preparation of Compound I Salt Form
[0126] The inventors of the present application have devoted a lot of effort to try to form corresponding salts with compound I using hippuric acid, D-tartaric acid, L-pyroglutamic acid, L-malic acid, methanesulfonic acid, phosphoric acid, sulfuric acid, fumaric acid, formic acid, and succinic acid as acid ligands, but no corresponding salts or crystals were formed. The experimental methods and experimental results are shown in Table 9.
[0127] Table 9
[0128]
[0129]
[0130]
[0131]
[0132] Example 3 Preparation of Compound I Maleate Salt
[0133] 400.5 mg of compound I and 149.0 mg of maleic acid were weighed into a 20-mL vial, 6.0 mL of acetone solvent was added, and the mixture was stirred at room temperature and then transferred to 40°C and stirred for 1 hour. The sample was then transferred to 5°C and stirred for 1.5 hours and then transferred to room temperature. The sample was transferred to -20°C and stirred for 16 hours, and then the sample was transferred to room temperature and evaporated while stirring for 6 hours. The suspension was centrifuged and vacuum dried at room temperature for 16 hours to obtain a solid.
[0134] After testing, the obtained solid was Form A, and its XRPD pattern was as follows: Figure 2 The XRPD data are shown in Table 10.
[0135] Thermogravimetric analysis / differential scanning calorimetry analysis of Form A is shown in Figure 3 As shown, the results show that when Form A is heated to 100°C, it has only a 0.11% mass loss and an endothermic peak begins to appear around 115.0°C.
[0136] Form A 1 H NMR results are as follows Figure 4 As shown, the results indicate that the molar ratio of maleic acid to compound I in Form A is 1:1, and no residual acetone solvent is detected in Form A.
[0137] Table 10
[0138] Pos.[°2θ] Rel.Int.[%] 9.52 2.03 10.44 1.53 12.82 3.99 15.85 1.04 17.17 1.98 17.51 1.03 19.08 100.00 19.56 22.18 19.99 2.63 20.72 3.47 20.95 8.17 21.45 1.51 23.07 8.89 23.58 2.04 24.33 0.43 24.77 0.72 25.86 0.96 26.12 1.14 26.47 1.21 27.18 3.21 28.89 1.65 29.10 1.28 30.06 6.57 31.16 0.24 31.61 2.92 32.41 0.56 33.90 0.27 34.44 0.23 35.53 0.10 38.19 0.20 38.91 3.73 39.67 0.51
[0139] Example 4 Preparation of Compound I Hydrochloride
[0140] Compound I (500 mg, 1.52 mmol) was dissolved in 1 mL of ethyl acetate. Under an ice bath, 3 mL of a solution of hydrogen chloride in ethyl acetate (c = 2.27 mol / L) was added dropwise. The mixture was stirred for 20 min and dried to obtain a white solid. The solid was ultrasonically washed twice with ether and filtered to obtain a white solid (517 mg, 1.42 mmol). The yield was 93.3%. 1 H NMR (300 MHz, CDCl 3 )δ12.26(s,1H),7.74(d,J=8.2Hz,2H),7.62(d,J=7.9Hz,2H),4.29(d,J=6.0Hz,2H),3.55(d,J=11.5Hz,2H),3.08(s,2H),2.75–2.47(m,2H),2.45–2.28(m,4H),2.23(s,3H),1.87(t,J=17.9Hz,4H),1.63(s,4H),1.51–1.29(m,1H). After testing, the obtained white solid was the hydrochloride crystal of compound I, named as Form B.
[0141] Example 5 Preparation of p-toluenesulfonate of Compound I
[0142] Weigh 301.3 mg of compound I and 181.5 mg of p-toluenesulfonic acid monohydrate into a 20-mL vial, add 12.0 mL of acetone solvent, stir at room temperature to dissolve, and after turbidity appears, transfer the sample to 40°C and continue stirring for 19 hours, centrifuge, and dry the obtained solid at room temperature for 8 hours to obtain a dry solid as Form C.
[0143] The XRPD pattern of Form C is as follows: Figure 5 The XRPD data are shown in Table 11.
[0144] Thermogravimetric analysis / differential scanning calorimetry analysis of Form C is shown in Figure 6 As shown, the results show that when the crystal form C is heated to 150°C, there is a 0.62% weight loss, and an endothermic peak begins to appear near 153.8°C.
[0145] Form C 1 H NMR results are as follows Figure 7 As shown, the results show that the molar ratio of toluenesulfonic acid to compound I in Form C is 1:1.
[0146] Table 11
[0147]
[0148]
[0149] Example 6 Preparation of Compound I Benzenesulfonate
[0150] Compound I (50 mg, 0.152 mmol) was dissolved in 1 mL of acetone, and benzenesulfonic acid (22.9 mg, 0.145 mmol) was added thereto. The mixture was reacted at 60°C for 48 h. Solid precipitation was observed. The reaction solution was filtered while hot, and the filter cake was ultrasonically washed twice with ether and filtered to obtain a white solid (61 mg, 0.126 mmol). The yield was 83%.
[0151] After testing, the obtained white solid was found to be Form D.
[0152] The XRPD pattern of Form D is as follows: Figure 8 The XRPD data are shown in Table 12.
[0153] Thermogravimetric analysis / differential scanning calorimetry analysis of Form D is shown in Fig. 9 As shown, the results show that when the crystal form D is heated to 150°C, there is a 0.11% mass loss, and an endothermic peak begins to appear around 130.7°C.
[0154] Table 12
[0155]
[0156]
[0157] Example 7 Preparation of Compound I Citrate
[0158] Compound I (65 mg, 0.198 mmol) was dissolved in 1 mL of ethyl acetate, and citric acid (36.1 mg, 0.188 mmol) was added thereto. The mixture was reacted at 60° C. for 24 h. Solid precipitation was observed. The reaction solution was filtered while hot, and the filter cake was washed twice with ether and a small amount of acetone to obtain a white solid (35 mg, 0.067 mmol) with a yield of 34%.
[0159] After testing, the obtained white solid was found to be Form E.
[0160] The XRPD pattern of Form E is as follows: Fig.10 The XRPD data are shown in Table 13.
[0161] Thermogravimetric analysis / differential scanning calorimetry analysis of Form E is shown in Fig.11 As shown, the results show that there is a 1.45% mass loss when heated to 100°C, and there is an endothermic peak at 85.8°C (peak temperature).
[0162] Table 13
[0163]
[0164]
[0165] Example 8 Preparation of Compound I Hydrobromide
[0166] Compound I (50 mg, 0.152 mmol) was dissolved in 1 mL of ether, and 48% aqueous hydrobromic acid solution (24.8 μL, 0.457 mmol) was added thereto at 0°C. A white solid was precipitated immediately. The reaction was carried out at room temperature for 2 h. The reaction solution was filtered, and the filter cake was ultrasonically washed twice with ether and filtered to obtain a white solid (58 mg, 0.142 mmol) with a yield of 93%.
[0167] After testing, the obtained white solid was found to be Form F.
[0168] The XRPD pattern of Form F is as follows: Fig.12 The XRPD data are shown in Table 14.
[0169] Thermogravimetric analysis / differential scanning calorimetry analysis of Form F is shown in Fig.13 As shown, the results show that Form F has a mass loss of 2.26% when heated to 150°C, and has two endothermic peaks at 72.2 and 172.7°C (peak temperatures).
[0170] Table 14
[0171]
[0172]
[0173] Example 9 Comparison of properties of the maleate, hydrochloride, p-toluenesulfonate, benzenesulfonate, citrate and hydrobromide salts of Compound I
[0174] The properties of maleate, hydrochloride, p-toluenesulfonate, benzenesulfonate, citrate and hydrobromide are shown in Table 15.
[0175] Table 15
[0176]
[0177]
[0178] The results showed that the maleate of Compound I and the hydrochloride of Compound I had good physicochemical stability and high yield.
[0179] Example 10 Hygroscopicity and humidity stability of crystal form A and crystal form B
[0180] The hygroscopicity of Form A and Form B was evaluated by DVS. Starting from 0% relative humidity (0% RH), the test collected the mass change percentage of Form A under constant temperature of 25°C as the humidity changed (0% RH-95% RH-0% RH). The DVS graph of Form A is shown in Fig.14 The test results are shown in Table 16, and the XRPD comparison diagram before and after the test is shown in Fig.15 The DVS diagram of Form B is shown in Fig.18 shown.
[0181] Table 16
[0182] Crystal form Weight gain after moisture absorption (25℃ / 80%RH) Crystalline Form A 0.331% Crystalline Form B 3.285%
[0183] The results show that the moisture-induced weight gain of crystal form A is small, and the crystal form does not change before and after the DVS test, which shows that it has good humidity stability.
[0184] Example 11 PLM Characterization of Form A
[0185] PLM characterization of Form A was performed, and the results are as follows Fig.16 The test results show that the particle size of Form A is about 10-50 μm, which is a flaky crystal.
[0186] Example 12 SEM Characterization of Form A
[0187] The crystal form A was characterized by SEM, and the results are as follows Fig.17 The results show that Form A is an irregular flaky crystal.
[0188] Example 13 Dynamic Solubility of Form A and Form C
[0189] When performing drug solubility testing to predict in vivo performance, it is important to simulate in vivo conditions as closely as possible. FeSSIF (simulated fed intestinal fluid) can simulate the in vivo environment, and the solubility tested in this medium is closer to the solubility in the human body environment.
[0190] About 20 mg of Form A was weighed into a 4-mL sample bottle, and 2 mL of the corresponding solvent was added, and the mixture was magnetically stirred at 37°C. Samples were taken and filtered using a 0.22 μm nylon membrane syringe filter at 2 h and 24 h, and the sample concentration in the filtrate was determined using HPLC. The filter cake was dried with nitrogen and then tested using XRPD.
[0191] About 20 mg of Form C (calculated as the free base of Compound I) was weighed into a 5-mL vial and dispersed in 4 mL of water, SGF, FaSSIF and FeSSIF, respectively. The mixture was rotated and mixed at 37°C for 1 hour, 2 hours, 4 hours and 24 hours. About 0.8 mL of the sample was centrifuged and filtered respectively. The solid was tested for XRPD, and the filtrate was tested for HPLC concentration and pH. The test results are shown in Table 17.
[0192] Table 17
[0193]
[0194] The results showed that compared with Form C, Form A had higher solubility in water and various biological solvents (>6.5 mg / mL), and the crystal form did not change before and after testing in different solvents.
[0195] The crystal form A provided by the present invention has a higher solubility, which is beneficial to improving the absorption of the drug in the human body and improving the bioavailability; in addition, the higher solubility can reduce the dosage of the drug while ensuring the efficacy of the drug, thereby reducing the side effects of the drug and improving the safety of the drug.
[0196] Example 14 Physicochemical Stability of Form A
[0197] After Form A was placed at 25°C / 60%RH and 40°C / 75%RH for 1 week and 2 weeks, and at 80°C for 24 hours, the physical and chemical stability of the samples were tested by XRPD and HPLC. The stability evaluation results are shown in Table 18, and the XRPD comparison before and after stability placement is shown in Fig.19 shown.
[0198] Table 18
[0199]
[0200] The results showed that the purity and crystal form of Form A did not change after being placed under 25°C / 60% RH and 40°C / 75% RH conditions for 1 week and 2 weeks, and the crystal form did not change after being placed at 80°C for 24 hours, indicating that Form A has good physicochemical stability under accelerated and harsh conditions.
[0201] Example 15 Light stability of Form A
[0202] Weigh 2 appropriate amounts of Form A into transparent glass bottles, seal one of them with tin foil, and then put the two glass bottles into a stability test box with their mouths closed. After 10 days, take them out to test the crystal form.
[0203] The results showed that the crystal form A did not change after being placed under strong light for 10 days, and the solid stability was good.
[0204] Example 16 Particle size distribution of Form A
[0205] Take an appropriate amount of Form A sample and put it into the dispersion unit, and test it three times according to the parameters shown in Table 8. The particle size distribution diagram of the third test is as follows: Fig. 20 The particle size distribution results of three tests are shown in Table 19.
[0206] Table 19
[0207] Number of tests Dv(10) micron Dv(50) micron Dv(90) micron 1 4.98 24.3 76.0 2 4.8 23.3 74.5 3 4.68 22.8 73.8
[0208] Example 17 Physicochemical Stability of Form C
[0209] After Form C was placed at 25°C / 60%RH and 40°C / 75%RH for 1 week and 2 weeks, the physical and chemical stability of the samples were tested by XRPD and HPLC. The stability evaluation results are shown in Table 20, and the XRPD comparison diagrams before and after stability placement are shown in Fig.21 shown.
[0210] Table 20
[0211]
[0212] The results showed that the purity and crystal form of Form C did not change significantly after being placed under 25°C / 60% RH and 40°C / 75% RH conditions for 1 week and 2 weeks, indicating that Form C has good physicochemical stability.
[0213] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A maleate salt of a compound represented by formula (I), 2. The maleate of the compound of formula (I) according to claim 1, It is characterized in that The molar ratio of the maleic acid to the compound of formula (I) is 1:
1.
3. The maleate salt of the compound of formula (I) according to claim 1, It is characterized in that The maleate salt is a crystalline solid.
4. A maleate salt of the compound of formula (I) according to claim 1, It is characterized in that The maleate salt crystals are anhydrous.
5. A maleate salt of the compound of formula (I) according to claim 1, Features At least one of the following: (i) using Cu-kα radiation, an X-ray powder diffraction pattern comprising 3 or more 2θ values selected from the group consisting of 9.52°±0.2°, 12.82°±0.2°, 19.08°±0.2°, 19.56°±0.2°, 19.99°±0.2°, 20.72°±0.2°, 20.95°±0.2°, 23.07°±0.2°, 23.58°±0.2°, 27.18°±0.2°, and 30.06°±0.2°; (ii) an X-ray powder diffraction pattern substantially as shown in FIG2 ; (iii) An endothermic peak begins to appear around 115.0°C.
